IMPLEMENTASI SOLAR CHARGING STATION DAN DIGITALISASI SISTEM LELANG HASIL PANEN UNTUK MENINGKATKAN JUMLAH PENGUNJUNG DI EMBUNG SENDANGTIRTO - Haeni Budiati; Lukas Agung Heriputranto; Liefson Jacobus (Jurnal Abdimas Bina Bangsa, 2023)
Sendangtirto Village is located in Kapanewon Berbah, Sleman D.I. Regency. Yogyakarta has an artificial reservoir/lake. The main objective of building a reservoir is to provide a conservation area and irrigation of rice fields. The existence of harvest sales activities through an auction system and the construction of joglos and gazebos around the embung, make the Sendangtirto embung worthy of becoming a tourist destination. Currently, the existence of the embung is not yet known to the wider public, besides that the public facilities available are still minimal. The PKM team took the title "Implementation of a Solar Charging Station and Digitalization of the Harvest Auction System to Increase the Number of Visitors at Embung Sendangtirto" and hoped to be able to overcome this problem. The Solar Charging Station was chosen because it uses renewable energy sources, is environmentally friendly and economical. The design is simple and easy to implement and operate. Meanwhile, to overcome the problem of the number of visitors, training and assistance will be provided in creating content on social media as a means of promotion. In addition, there is a need to create a digital harvest auction recording system. Through this PkM activity, it is hoped that it can provide education on the use of renewable energy for the community, increase horticulture sales from farmers and increase the number of visitors at the Sendangtirto reservoir.